SOCIETAL PARTICIPATION ON MANAGING TOURISM OF RINJANI NATIONAL PARK IN THE EXAMPLE OF SEMBALUN LAWANG, LOMBOK TIMUR - Junaidi, Muhammad Adi; Basri, Hasan; Fahrurrozi, Muh.; Rahadi, Irwan; Ramli, Muhammad; Zaitun, Zaitun; Sugandi, Yogi Birrul Walid; Pauzi, Muh Hilmi; Sukran, Muhammad Ali (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
Sembalun Lawang Village is one of Mount Rinjani National Park (TNGR) entrances. This study aims to review the local participation of Sembalun Lawang in the management of climbing tourism of Rinjani National Park. This research employs descriptive methods with observation, interview, documentation, and literature studies. After the data is collected, the next step is to analyze the data using Miles and Huberman models; data collection, data reduction, data presentation and conclusion withdrawal. The results showed that community participation in managing the climbing of Rinjani National Park had partition differences at all stages. At the planning stage, the community has never been involved in identifying problems and decision-making due to the unaccountability of information of understandable climbing. The stage of community involvement is high as many people are interested in climbing tourism for businesses such as lodging businesses, climbing equipment rental businesses, restaurant businesses, souvenir businesses, service businesses (porters, guides, trekking organizers). Participation is classified, and some are not yet maximally applied.